Decolonization in, of and through the archival “moving images” of artistic practice - Oliveira, Ana Balona de (2016)
This essay investigates the ways in which contemporary artistic practices have been working towards an epistemic and ethico-political decolonization of the present by means of critical examinations of several sorts of colonial archives, whether public or private, familial or anonymous. Through the lens of specific artworks by the artists Ângela Ferreira, Kiluanji Kia Henda, Délio Jasse, Daniel Barroca and Raquel Schefer, this essay examines the extent to which the aesthetics of these video, photographic and sculptural practices puts forth a politics and ethics of history and memory relevant to thinking critically about the colonial amnesias and imperial nostalgias which still pervade a post-colonial condition marked by neo-colonial patterns of globalization and by uneasy relationships with diasporic and migrant communities. Attention will be paid to the histories and memories of the Portuguese dictatorship and colonial empire, the liberation wars / the “colonial” war fought in Angola, Mozambique and Guinea-Bissau between 1961 and 1974, the Carnation Revolution in Portugal in 1974, the independence of Portugal’s former colonies between 1973 and 1975, and the mass “return” of Portuguese settlers from Angola and Mozambique in 1975, without losing sight of apartheid South Africa and the ways in which the Cold War played out on the African continent.